2014
DOI: 10.1088/0741-3335/56/3/035007
|View full text |Cite
|
Sign up to set email alerts
|

Freak waves and electrostatic wavepacket modulation in a quantum electron–positron–ion plasma

Abstract: The occurrence of rogue waves (freak waves) associated with electrostatic wavepacket propagation in a quantum electron-positron-ion plasma is investigated from first principles. Electrons and positrons follow a Fermi-Dirac distribution, while the ions are subject to a quantum (Fermi) pressure. A fluid model is proposed and analyzed via a multiscale technique. The evolution of the wave envelope is shown to be described by a nonlinear Schrödinger equation (NLSE). Criteria for modulational instability are obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 55 publications
2
27
0
Order By: Relevance
“…8,39 Various relevant theoretical investigations have been proposed, predicting excitations that are yet to be detected. 17,[42][43][44] Considering the possibility for experimental confirmation (realization) of our predictions in the laboratory, we note that the present model becomes relevant for ultra-high densities, when both degeneracy and relativistic effects come into play. For instance, an one-dimensional density n 0 % 10 11 m À1 , corresponding to n 0 % 0:1 (and a 3D equivalent of n 3D % 10 33 m À3 ), is not at all inconceivable in view of the already available laser-plasma compression technology.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…8,39 Various relevant theoretical investigations have been proposed, predicting excitations that are yet to be detected. 17,[42][43][44] Considering the possibility for experimental confirmation (realization) of our predictions in the laboratory, we note that the present model becomes relevant for ultra-high densities, when both degeneracy and relativistic effects come into play. For instance, an one-dimensional density n 0 % 10 11 m À1 , corresponding to n 0 % 0:1 (and a 3D equivalent of n 3D % 10 33 m À3 ), is not at all inconceivable in view of the already available laser-plasma compression technology.…”
Section: Discussionsupporting
confidence: 51%
“…The value of Q/P is proportional to the (square) wavenumber j; in other words, a perturbation may become unstable in the window ½0; j. Furthermore, the ratio Q/P is related to the inverse width of a bright pulse of given amplitude w 0 : to see this, recall that a bright soliton solution of the NLSE (17) in the form w 0 sech nÀu e s L satisfies the relation w 0 L $ ðP=QÞ 1=2 . Therefore, for given w 0 (prescribed, i.e., by the lump of energy launched in the system), an envelope soliton will be wider (i.e., larger L) if Q/P acquires smaller values, and vice versa.…”
Section: Localized Envelope Structuresmentioning
confidence: 99%
“…In particular, there is no a priori methodological reason to quickly discard the time derivative of the pressure, manifesting in the ∝ ∂n e /∂t contribution in the electrons force equation in Eq. (9). Note also that we do not discard the electrons' convective derivative, because after restoring physical coordinates it can be shown that the Fermi pressure vanishes in the inertialess limit (formally m e /m i → 0).…”
Section: Hydrodynamic Modelmentioning
confidence: 99%
“…For instance, 1D dense plasmas are of relevance to the target normal sheath acceleration mechanism [2] produced during the irradiation of solid targets with a high-intensity laser available with coherent brilliant x-ray radiation sources [3]. Furthermore, the nonlinear dynamics of 1D degenerate plasmas shows a rich variety of behavior; applications include the dense quantum diode [4], the electron-hole plasma injected into quantum wires [5], the 1D fermionic Luttinger liquid [6], breather-mode oscillations in 1D semiconductor quantum wells [7], Lagrangian structures in dense 1D plasmas [8], and 1D nonlinear envelope modes in dense electron-positronion plasmas [9], among others. Sagdeev's pseudopotential method was used to study the propagation of wave structures of arbitrary amplitude in a relativistically degenerate electron-positron-ion plasmas in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…As W increases, nonlinear phenomena start showing up, enabling, for instance, wave-wave couplings. Although only recently investigated in plasmas, the occurrence of rogue waves has been raised in various plasma conditions [29][30][31]. Rogue waves have been studied in many dynamical systems, and are known to the general public by the observation and study of rogue or freak waves that suddenly appear in the ocean as large isolated waves.…”
Section: Effect Of Plasma Wavesmentioning
confidence: 99%